A Dual Model of Ownership - Gürgüç, Zeynep; Learney, Robert M. (Frontiers in Blockchain, 2020)
The transparency and visibility engendered in Distributed Ledger Technology allows, for the first time, disparate stakeholders to agree on common resource existence, ownership, and rules of exchange, while keeping the coordination costs comparatively low with respect to earlier methods. This infrastructure can finally facilitate a self-organising market mechanism, where people can decide upon the market rules themselves and potentially self-select into any particular marketplace dependent upon their personal beliefs and preferences. Reinventing the apparatus of the economy upon shared distributed infrastructure may finally allow the emergence of actual shared ownership, unlike the existing systems where short-term rentals or access-based consumption are often confused with sharing and social exchange.